Language Learning Strategy Used by Nursing Academy Students in Learning English - Nanda Rosi Parera (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2022)
The objectives of this research were to describe the language learning strategies used by nursing academy students in learning English and to describe the classification of language learning strategies used by higher and lower score students in learning English. A questionnaire was used as the instrument for this research. The participants of this research were 57 students of the nursing academy (AKPER Bina Insani Sakti Sungai Penuh). The researcher used the Strategy Inventory for Language Learning (SILL) by Oxford (1990) to determine the student’s language learning strategy. The result revealed that the students used all strategies (memory, cognitive, compensation, metacognitive, affective, and social), which were categorized as high and medium. The highest mean value was Metacognitive strategies (3.64). The higher scores of nursing academy students also used all six learning strategies, with the highest mean values referring to Metacognitive and Social strategies (4.10). On the other hand, the lower score students sometimes used and generally did not use the learning strategies in their learning activities. which is shown with the highest mean value was the memory strategy (3.02). As a result, it is simply categorized as medium strategy employed by students.